2014
DOI: 10.5194/tc-8-1539-2014
|View full text |Cite
|
Sign up to set email alerts
|

Elevation and elevation change of Greenland and Antarctica derived from CryoSat-2

Abstract: Abstract. This study focuses on the present-day surface elevation of the Greenland and Antarctic ice sheets. Based on 3 years of CryoSat-2 data acquisition we derived new elevation models (DEMs) as well as elevation change maps and volume change estimates for both ice sheets. Here we present the new DEMs and their corresponding error maps. The accuracy of the derived DEMs for Greenland and Antarctica is similar to those of previous DEMs obtained by satellite-based laser and radar altimeters. Comparisons with I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
364
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(410 citation statements)
references
References 62 publications
14
364
0
Order By: Relevance
“…While the datasets are self-consistent over this period, each likely reflects conditions that are unchanging over a different time scale. Observations show that the study area is not undergoing rapid thinning (Pritchard et al, 2009;Helm et al, 2014), suggesting that the surface geometry has been in a relatively steady state over perhaps many decades. However, while the velocity observations in the study area are consistent over multiple years, large changes in ice motion have been observed elsewhere on the ice sheet over time periods much shorter than the decadal scale that is likely represented by the surface geometry (Rignot and Kanagaratnam, 2006;Joughin et al, 2010).…”
Section: Discussion Force Balance and Surface Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…While the datasets are self-consistent over this period, each likely reflects conditions that are unchanging over a different time scale. Observations show that the study area is not undergoing rapid thinning (Pritchard et al, 2009;Helm et al, 2014), suggesting that the surface geometry has been in a relatively steady state over perhaps many decades. However, while the velocity observations in the study area are consistent over multiple years, large changes in ice motion have been observed elsewhere on the ice sheet over time periods much shorter than the decadal scale that is likely represented by the surface geometry (Rignot and Kanagaratnam, 2006;Joughin et al, 2010).…”
Section: Discussion Force Balance and Surface Velocitymentioning
confidence: 99%
“…We use the CryoSat-2 DEM (Helm et al, 2014) to define the ice sheet surface over the study area. It is posted at 1 km resolution.…”
Section: Study Area and Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the lack of systematic sea-ice thickness measurements in the Southern Hemisphere. There are only few in situ data sets from upwardlooking sonars (only Weddell Sea; e.g., Harms et al, 2001;Behrendt et al, 2013), drillings (e.g., Lange and Eicken, 1991;Ozsoy-Cicek et al, 2013;Wadhams et al, 1987;Perovich et al, 2004), electromagnetic methods (Haas, 1998;Weissling et al, 2011;Haas et al, 2008) and airborne altimetry (e.g., Dierking, 1995;Leuschen et al, 2008). Those data are distributed unevenly in location, coverage and time and do not allow for the estimation of seasonal and interannual sea-ice volume changes.…”
Section: Introductionmentioning
confidence: 99%
“…These are: repeat altimetry (Csathó et al 2014), DEM differencing (Wang and Kääb 2015), and a combination of these two Helm et al 2014). As shown in Table 1, each of the methods has advantages and disadvantages with regards to temporal and spatial coverage.…”
Section: Elevation and Volume Changesmentioning
confidence: 99%